Colin Kirkby Peace. (19th November 2021) - Rossdale, Peter; Hunt, Michael; Ricketts, Sidney; Digby, Nick Wingfield; Greet, Tim
Abstract : An innovative and enthusiastic equine veterinary surgeon who was also passionately involved with the sport of modern pentathlon in both Britain and Canada.